2014
DOI: 10.1007/s13760-014-0335-6
|View full text |Cite
|
Sign up to set email alerts
|

Fasciculations in human hereditary disease

Abstract: Fasciculations are a manifestation of peripheral nerve hyperexcitability in addition to myokymia, neuromyotonia, cramps, or tetany. Fasciculations occur in hereditary and non-hereditary diseases. Among the hereditary diseases, fasciculations are most frequently reported in familial amyotrophic lateral sclerosis (FALS), and spinal muscular atrophy (SMA). Among the non-hereditary diseases, fasciculations occur most frequently in peripheral nerve hyperexcitability syndromes (Isaac's syndrome, voltage-gated potass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
0
3
0
2
Order By: Relevance
“…Cramps are frequent in polyneuropathies (Table ), including uraemic , diabetic , chemotherapy‐induced and inherited polyneuropathies . Axonal excitability studies in these neuropathies have suggested that this higher prevalence of cramps might be related to increased axonal excitability.…”
Section: Neuropathic Conditionsmentioning
confidence: 99%
“…Cramps are frequent in polyneuropathies (Table ), including uraemic , diabetic , chemotherapy‐induced and inherited polyneuropathies . Axonal excitability studies in these neuropathies have suggested that this higher prevalence of cramps might be related to increased axonal excitability.…”
Section: Neuropathic Conditionsmentioning
confidence: 99%
“…The patient did not fit with criteria for the cramps‐fasciculation syndrome or amyotrophic lateral sclerosis. Fasciculations may be seen in many hereditary neurological disorders, and may remain an unspecific finding . It is possible that his symptoms might be due to instability of peripheral motor nerves due to his slowly developing AMN, yet this remains speculative.…”
Section: Discussionmentioning
confidence: 99%
“…Krankhafte Ursachen von Faszikulationen sind hingegen vielfältig [22,24,25]. Polyneuropathie, hereditäre Neuropathien und zervikale oder lumbale Radikulopathien) zeigt sich bei der Erfassung von Faszikulationen im Ultraschall ein höherer Faszikulationsgrad für ALS-Patienten und ein anderes Verteilungsmuster der Faszikulationen zwischen diesen beiden Gruppen [27].…”
Section: Merkeunclassified